Biosynthesis of Melanin Nanoparticles for Photoacoustic Imaging Guided Photothermal Therapy. Issue 14 (29th December 2022) - Fu, Meijun; Yang, Yuping; Zhang, Zhaomeng; He, Yaling; Wang, Yuanyuan; Liu, Chenxing; Xu, Xiaohong; Lin, Jing; Yan, Fei
Abstract: Photothermal therapy (PTT) has attracted considerable attention in recent years due to their unique advantages in minimal invasiveness and spatiotemporal selectivity. However, the fabrication procedures of PTT agents frequently require complex chemical and/or physical methods that involves harsh and environmentally hazardous conditions. Here, a genetically engineered bacterium is developed to synthesize melanin nanoparticles under mild and environmentally friendly conditions. The biosynthetic melanin nanoparticles exhibit excellent biocompatibility, good stability, and negligible toxicity. In addition, the biosynthetic melanin nanoparticles have strong absorption at near‐infrared (NIR) region and higher photothermal conversion efficiency (48.9%) than chemically synthesized melanin‐like polydopamine nanoparticles under an 808 nm laser irradiation. Moreover, the results show that the biosynthetic melanin nanoparticles have excellent photoacoustic imaging (PAI) performance and can be used for PAI guided PTT in vivo. In conclusion, the study provides an alternative approach to synthesize PTT agents with broad application potential in the diagnosis and treatment of cancer. Abstract : An alternative approach to synthesize melanin nanoparticles is employed by expressing a heterologous tyrosinase gene in Escherichia coli . The biosynthetic melanin nanoparticles have high photothermal conversion efficiency with excellent photoacoustic imaging performance and biocompatibility, which can be used as phototheranostic agents to ablate tumors.